2020
DOI: 10.1177/0706743720938598
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of COVID-19 in the Italian Population: Anxiety, Depression, and Post-traumatic Stress Symptoms

Abstract: The first case of COVID-19 in Italy emerged at the end of January 2020. 1 Following a series of increasingly severe restrictions, a new decree on March 9, 2020, imposed home lockdown on the entire nation. 2 The COVID-19 outbreak, similarly to previous epidemics, can trigger psychological disorders such as anxiety, depression, and post-traumatic stress disorder (PTSD) in exposed individuals in the short as well as in the long-term. 3 This study aimed to investigate the prevalence of posttraumatic stress symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 4 publications
6
55
3
8
Order By: Relevance
“…Remarkably, anxiety symptoms in parents were strictly related to perceived financial problems [19] and with the concern about contracting COVID-19. This concern did not correlate with age, with knowing someone affected or, conversely to previous data [14,15], with female sex. Furthermore, no correlation was found between anxiety and concern about rehabilitation activity suspension, in stark contrast with the findings of another Italian cross-sectional study, which found this association in a population of 84 caregivers of children with a wide range of neurodevelopmental disabilities [23].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, anxiety symptoms in parents were strictly related to perceived financial problems [19] and with the concern about contracting COVID-19. This concern did not correlate with age, with knowing someone affected or, conversely to previous data [14,15], with female sex. Furthermore, no correlation was found between anxiety and concern about rehabilitation activity suspension, in stark contrast with the findings of another Italian cross-sectional study, which found this association in a population of 84 caregivers of children with a wide range of neurodevelopmental disabilities [23].…”
Section: Discussioncontrasting
confidence: 91%
“…During this COVID-19 emergency, different authors have drawn attention to disabilities, claiming the need for inclusivity [ 11 ], warning about the risk of future increased burden of care due to reduced functional outcomes [ 3 ] and pandemic-related mental health risks [ 10 ], and have suggested an urgent rethinking about the current and future management of children with disability [ 12 , 13 ]. Psychological distress related to COVID-19 has been studied in the Italian population [ 14 , 15 ], and the implications of this pandemic for the mental health of young people has been outlined [ 16 , 17 ]. Additionally, the traumatic effects on families of pandemics and of the associated disease-containment measures have been confirmed globally [ 18 , 19 ], highlighting the need to focus on the most vulnerable families [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports that enforced isolation has a significant impact on many aspects of people's lives, generating substantial psychological stress which, in some instances, can even trigger a range of psychological problems (Brooks et al, 2020;Castelli et al, 2020;Mazza et al, 2020). Moreover, social isolation increases the risk of morbidity and mortality, while social support contributes to mental health (Pantell and Shields-Zeeman, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Coronavirus disease , which is caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that originated in the Hubei province of China in December 2019, has spread rapidly worldwide (Chan et al, 2020) and been declared a global pandemic by the World Health Organization (World Health Organization [WHO], 2020). The widespread contagion and lockdown of the COVID-19 have caused considerable mental health problems such as anxiety, depression, and post-traumatic stress symptoms (Castelli et al, 2020;Talevi et al, 2020;Torales et al, 2020;Vindegaard and Benros, 2020). Different levels of psychological distress may appear depending on the healthcare workers (Di Tella et al, 2020;Lai et al, 2020;Li et al, 2020;Vindegaard and Benros, 2020), the elderly (Yang et al, 2020), and the presence of underlying disease (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%